Obtencion de Ovocitos de Llamas (lama glama) en la Planta de Faenamiento del GAD Municipal del Cantòn Saquisili. - Yanqui Chicaiza, Segundo Jaime (2018)
This investigation was carried out in the Biotecnología Laboratory of Reproduction which belongs to the Veterinary Medicine Major of the Technical University of Cotopaxi. Eight pairs of ovaries of discarded llamas were used which were acquired post-mortem at the plant of slaughter of the municipal GAD from Saquisili Canton, the ovaries obtained were identified and transported in a hermetic bag with 0.9% sodium chloride at a temperature of 37 ° C. Two techniques were used to extract the oocytes: follicular aspiration, and slicing. The oocytes obtained by the two techniques were classified into four groups of type A, B, C, and D, according to the integrity criterion of the layers of cells in the cluster and the characteristics of the cytoplasm of the oocyte, by the method of follicular aspiration, 9 type A oocytes are obtained, which means 33% and 4 type A oocytes by the follicular slicing method of the total using the follicular aspiration method, it is collected more quantity of oocytes in quantity and quality than the other method. Concluding that the effectiveness of the technique of follicular aspiration, since a more significant amount of type A oocytes were obtained that present with cumulus cells with multiple layers and with a homogeneous and transparent cytoplasm, they are visible oocytes formed with a non-irradiated crown that belongs to mature quality.